Pengaturan Ideal tentang Pengelolaan Daerah Aliran Sungai di Indonesia (Studi di Sungai Serang Kabupaten Kulon Progo) - Nita Ariyani; Dwi Oktafia Ariyanti; Muhammad Ramadhan (Jurnal Hukum IUS QUIA IUSTUM, 2020)
Watershed management is closely related to regulations on the affairs of local governance, water resources, spatial planning, as well as soil and water conservation. All forms of regulation relating to watershed management must be strictly regulated as the legal basis for watershed management in Indonesia. This study aims to identify, understand, and analyze the juridical constraints faced in managing watersheds in Indonesia and to analyze the ideal juridical regulatory model for watershed management in Indonesia. This research was conducted using normative juridical research, by focusing on testing the implementation of rules or norms in positive law. The results of the study show juridical constraints in watershed management in Indonesia relating to the Revocation and Substitution of the Water Resources Law; the lack of synchronization between the Water Resources Law, the Regional Government Law and the Soil and Water Conservation Law. Therefore, the authors formulate the ideal form of watershed management arrangements, among others by taking quick and effective steps through district / city regional policies while continuing to synchronize efforts through policies in the form of mandates and tasks of assisting watershed management sub-affairs.